2005
DOI: 10.2307/40166813
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Management of Shiny Cowbirds (Molothrus bonariensis) and Endangered Yellow-Shouldered Blackbirds (Agelaius xanthomus) in Puerto Rico

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. University of California Press and AmericanOrnithologists' Union are collaborating with JSTOR to digitize, preserve and extend access to Ornithological Monographs.Abstract.-Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Hence, evaluating Shiny Cowbird densities and eventually controlling Shiny Cowbird populations might be considered in future conservation plans for Yellow Cardinals. Control strategies on brood parasites have improved the reproductive success of threatened species in the past (Cruz et al 2005, Krabbe et al 2011, Hartmann et al 2017. These studies have shown that trapping cowbirds near host nesting areas and cowbird feeding areas, as well as shooting cowbirds, resulted in marked population increases of the threatened host species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, evaluating Shiny Cowbird densities and eventually controlling Shiny Cowbird populations might be considered in future conservation plans for Yellow Cardinals. Control strategies on brood parasites have improved the reproductive success of threatened species in the past (Cruz et al 2005, Krabbe et al 2011, Hartmann et al 2017. These studies have shown that trapping cowbirds near host nesting areas and cowbird feeding areas, as well as shooting cowbirds, resulted in marked population increases of the threatened host species.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, evaluating Shiny Cowbird densities and eventually controlling Shiny Cowbird populations might be considered in future conservation plans for Yellow Cardinals. Control strategies on brood parasites have improved the reproductive success of threatened species in the past (Cruz et al 2005, Krabbe et al 2011, Hartmann et al . 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Brood parasitism by Shiny Cowbirds reduces the breeding success of their hosts in several ways. First, parasite females peck and puncture host eggs during parasitic and non-parasitic visits, reducing clutch size and increasing the probability of nest abandonment (Post and Wiley, 1977b;Cruz and Andrews, 1997;Kattan, 1998;Reboreda, 1998, 2002;Mermoz and Reboreda, 1999;Sackmann and Reboreda, 2003;Cruz et al, 2005;Astié and Reboreda, 2009;Dominguez et al, 2015). Second, parasite eggs may interfere with host incubation lowering the hatching success of the remaining host eggs (Wiley, 1985;Woodworth, 1997;Reboreda, 2006, Tuero et al, 2007).…”
Section: Impactsmentioning
confidence: 99%
“…In the Antilles, three endemic species, the Bahamas Oriole (Icterus northropi; Price et al, 2011), the Yellowshouldered Blackbird (Cruz et al, 2005) and the Puerto Rican Vireo (Woodworth, 1997) suffer the joint pressure of anthropogenic habitat loss and brood parasitism by the Shiny Cowbird. Two of these species are threatened globally: the Bahamas Oriole (critically endangered) and Yellow-shouldered Blackbird (endangered) (IUCN, 2018).…”
Section: Impactsmentioning
confidence: 99%
See 1 more Smart Citation